Youth’s Interests in Professions a Soci-Field Study for the City of Baghdad - Yonis, Dr. Hani Ahmed (International Journal of Humanities and Education Development (IJHED), 2021)
Paying attention to the affairs of young people, their circumstances, their attitudes, and undoubtedly about work and the practice of a certain profession, helps to identify their reality, aspirations, problems, and the reasons that motivate them to go to a particular job, stay away from the other, and fulfill their various needs. The importance of the study lies in the noticeable increase in interest in youth, and the issue of youth and their work has become one of the important topics, due to the effective and influential role they play in the progress and development of societies and nations. A special issue that the researcher needs in his theoretical and practical study to collect scientific facts. The study included an intentional sample of young people and others who are able to work in different professions, whose ages range between (18-46) years only. The city of Baghdad was chosen because it is one of the millions of cities in the world and from the various governorates of the country. The study aimed to:1- Identifying the trends and motives of young people towards professions.2- Knowing the reasons that make a particular profession higher than others.3- Identifying the hierarchical order of the position of professions in Baghdadi society.This has shown the most important results of the study objectives:· The first objectiveFinancial / high wages for his work.Psychological / the individual's desire to achieve social relations and respect for others.Social / Achieving a prestigious social position in society.· The second objective The study concluded that there are reasons for young people’s motives towards choosing a profession related to the nature of their personal qualifications on the one hand, and what they get (financially and morally) from this profession, as follows:· High wages· Availability of opportunities for advancement and development· Profession stability and stability in general· Less risks and problems· Social relations· Lack of effortThe third objective occupied the first five ranks of the hierarchy of jobs for their priority and importance, which are as follows (university professor, doctor, engineer, teacher, lawyer, officer, public servant, ...etc. This shows the respondents' interest in governmental jobs for economic and social motives. The most important recommendation has been shown in the study: creating a balance between workers in the field of professional work and workers in the field of professional self-employment in order to advance sound development plans, through development programs presented by the media. employees in other professional sectors.